Biodiversity and conservation values of the serpentine ecosystems in Spain: Sierra Bermeja (Malaga province) - José Gómez Zotano, Felipe Román Requena; Noelia Hidalgo Triana, Andrés V. Pérez Latorre (Boletín de la Asociación de Geógrafos Españoles, 2014)
Resumen